2018
DOI: 10.1007/s00259-018-4076-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of chemokine receptor CXCR4 expression in culprit and nonculprit coronary atherosclerotic plaque using motion-corrected [68Ga]pentixafor PET/CT

Abstract: PurposeThe chemokine receptor CXCR4 is a promising target for molecular imaging of CXCR4+ cell types, e.g. inflammatory cells, in cardiovascular diseases. We speculated that a specific CXCR4 ligand, [68Ga]pentixafor, along with novel techniques for motion correction, would facilitate the in vivo characterization of CXCR4 expression in small culprit and nonculprit coronary atherosclerotic lesions after acute myocardial infarction by motion-corrected targeted PET/CT.MethodsCXCR4 expression was analysed ex vivo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Hyafil et al reported from a preclinical study that the CXCR4 protein was expressed in macrophage-rich arterial tissues, and demonstrated great potential for [ 68 Ga]Pentixafor PET to specifically recognize inflamed atherosclerotic lesions [ 18 ]. In another recent study, Derlin et al demonstrated that the [ 68 Ga]Pentixafor PET signal intensively accumulated in culprit coronary atherosclerotic plaques of patients with recent acute myocardial infarction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyafil et al reported from a preclinical study that the CXCR4 protein was expressed in macrophage-rich arterial tissues, and demonstrated great potential for [ 68 Ga]Pentixafor PET to specifically recognize inflamed atherosclerotic lesions [ 18 ]. In another recent study, Derlin et al demonstrated that the [ 68 Ga]Pentixafor PET signal intensively accumulated in culprit coronary atherosclerotic plaques of patients with recent acute myocardial infarction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, [ 68 Ga]Pentixafor demonstrated its potential for atherosclerotic plaque imaging not only because the CXCR4 protein is expressed at various cell types related to atherogenesis [ 12 , 30 34 ] and particularly the intensive co-localization of CXCR4 expression and macrophages ensures an adequate radio-signal for PET imaging, but also importantly, compared to 18 F-FDG, low myocardial uptake of 68 Ga-pentixfor could enable coronary imaging without specific patient preparation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the hypothesis that CXCR4 signal reports the level of endothelial injury in atherosclerosis, we compared 64 Cu-DOTA-vMIP-II to 64 Cu-DOTA-FC131, a CXCR4 specific tracer. Although PET signals arising from CXCR4-specific tracer is already reported in atherosclerosis (41)(42)(43)(44), the plaque characteristics, or biological parameters of plaque activity, that may or may not correlate with its PET signal are still not fully understood. Similar to studies with the vMIP-II tracer ( Fig.…”
Section: Cxcr4 Specific Pet Tracer Also Accumulates In Plaque Ecs Andmentioning
confidence: 99%
“…11C-PK11195 is able to image intraplaque haemorrhage in recently symptomatic carotid plaques 44 as well as active disease in large-vessel vasculitis, while CXCR4 has recently shown promise for the distinguising culprit and non-culprit coronary plaques in ST-elevation myocardial infarction. 45…”
Section: Positron Emission Tomography: Other Radiotracersmentioning
confidence: 99%